Clearance of amyloid‐beta with bispecific antibody constructs bound to erythrocytes. Issue 1 (27th August 2020) - Taylor, Ronald P.; Lindorfer, Margaret A.; Atkinson, John P.
Abstract: We propose use of bispecific monoclonal antibody (mAb) complexes bound to erythrocytes to redress the lack of efficacy of anti‐amyloid beta mAbs in Alzheimer's disease treatment. Our paradigm leverages erythrocyte complement receptor 1 to promote rapid and quantitative removal of amyloid beta from the circulation, and its subsequent removal from the brain as well.